Tan Sing Tian (陳成典): The Lost Majoor der Chinezen of Surabaya (1904-1906) and His Influence Towards the City - Santoso, Christopher Jason (Universitas Gadjah Mada, 2025)
Chinese settlements in Surabaya City have been evoked leastwise from Admiral Zheng He’s expedition to Java Island in the fifteenth century. After that, the Chinese people who mainly men assimilated and married with indigenous people, performing interracial marriage for centuries. Few Chinese people obtained power from local kingdoms, like in Melaka or Banten to control and bridge Chinese people towards the ruler. Soon during VOC establishment and Dutch colonialism era, the practice of Chinese officers was inherited yet and spread to all big cities and towns in Indonesia. One of the Chinese officers in Surabaya, Tan Sing Tian served the city from young age until his eternal rest. The information about him was genuinely limited to the current situation or even in scientific papers. This paper challenged itself to expose any information about Tan Sing Tian as the lost Majoor der Chinezen at Surabaya (1904-1906) and to understand his influence towards Surabaya City. The methodology of this paper is a historical research method with archives (books, magazines, and/or newspapers) as the main resource of the research. This research found that Tan Sing Tian is not merely a Chinese officer, rather humanist, philanthropist, and a donor of Kong Sie Poo Gie, cultural council on promoting acculturation and tolerance. This paper recommends a new archaeological and social exploration about Tan Sing Tian’s physical dignity and return of Tan Sing Tian’s equipment from The Netherlands.